Adult Onset Still's Disease - current state of knowledge - Centkowska, Anna; Wagner-Bieleń, Natalia Katarzyna; Zwierzchowska, Martyna; Antoniak, Agata; Jocz, Anna Maria; Banaśkiewicz, Joanna Karina; Żyta, Aleksandra Maria; Dąbrowska, Gabriela Helena; Żmijewska, Maria Anna; Ziółkowski, Jakub (Journal of Education, Health and Sport, 2025)
Introduction: Adult-onset Still’s disease (AOSD) is a rare systemic inflammatory disorder of unknown etiology. AOSD lies at the crossroads of innate and adaptive immunity, highlighting the complexity of its pathogenesis. The heterogeneous clinical expression and the lack of specific diagnostic markers contribute to the difficulties in achieving a rapid and accurate diagnosis, necessitating a careful differentiation to exclude malignancies, infections, and other inflammatory conditions. There is no universally established treatment protocol, as new therapeutic options continue to emerge. Aim of the study: The study aim is to analyse and summarize current state of knowledge about diagnosis and treatment strategies of Adult Onset Still’s Disease. Methodology: The PubMed database was searched to find scientific articles published between 2020-2025 with free full text available in which the term "Still’s disease" appears in the title or keywords. Conclusions: Adult-Onset Still’s Disease is a complex autoinflammatory disorder driven by a dysregulated cytokine storm, with infections and genetic predispositions implicated as triggers. It presents variably, from systemic inflammation to chronic arthritis, and can lead to severe complications. While traditional treatments like NSAIDs, corticosteroids, and DMARDs have been used, biologic therapies targeting IL-1 and IL-6 have significantly improved outcomes. Ongoing research aims to refine diagnostics, identify biomarkers, and develop personalized treatments.